Evaluation of first hospital entry and hospitalization related prescription polypharmacy targeting patients of fifty years old and more at a general hospital, Duhok, Iraq: Polypharmacy in elderly patients (Journal of Ideas in Health, 2024)
Background: Polypharmacy is the intake of ≥ 5 medications. This study evaluates the prevalence of polypharmacy among elderly patients hospitalized during October 2023 at Azadi Hospital in Duhok, Iraq.Methods: This was a retrospective cross-sectional study. The files of 373 patients aged ≥ 50 years were reviewed for the occurrence of polypharmacy (5 medications), major polypharmacy (6-9 medications) and excessive polypharmacy (≥ 10 medications) as well as their disease conditions.Results: The 373 patients received 5 to 10 medications at first hospital entry, and during hospitalization (1-29 days), 220 (58.98%) of them received 5 to 12 medications. Cardiovascular disorders (44.04%) were the most encountered conditions in the hospitalized patients, followed by endocrine disorders (26.4%) and gastrointestinal disorders (8.14%). Polypharmacy occurred in 63 (16.89%) patients on the first day of hospital entry and in 73 (19.57%) during the hospitalization period. Major and excessive polypharmacy occurred among 90 (24.13%) and 2 (0.54%) of patients at the first entry and among 129 (34.58%) and 18 (4.83%) patients during the hospitalization, respectively. During hospitalization, polypharmacy significantly (Chi squared=22.655; df=1; p=1.9387˟10-6) increased by 17.43% when compared to that of the first hospital entry. The most commonly used medications at the first hospital entry were paracetamol (17.18%) followed by antibiotics (11.8%). During hospitalization the most commonly used medications were antibiotics (13.52%) followed by proton pump inhibitors (11.43%).Conclusion: The prevalence of polypharmacy was high among elderly hospitalized patients. This condition might increase the risk of potential drug-drug interaction and the intake of inappropriate medications. Alerting clinicians about the significance of polypharmacy is necessary in prescribing and deprescribing medications to hospitalized elderly patients.
Keywords: Polypharmacy, Drug Interaction, Elderly, Prescription Medications, Disease Conditions, Iraq